Thiolene-based microfluidic flow cells for surface plasmon resonance imaging - Sheppard, Gareth (American Institute of Physics, 2011)
Thiolene-based microfluidic devices have been coupled with surface plasmon resonance imaging (SPRI) to provide an integrated platform to study interfacial interactions in both aqueous and organic solutions. In this work, we develop a photolithographic method that interfaces commercially available thiolene resin to gold and glass substrates to generate microfluidic channels with excellent adhesion that leave the underlying sensor surface free from contamination and readily available for surface modification through self-assembly. These devices can sustain high flow rates and have excellent solvent compatibility even with several organic solvents. To demonstrate the versatility of these devices, we have conducted nanomolar detection of streptavidin-biotin interactions using in situ SPRI.